The linearity of optical tomography: sensor model and experimental verification - Mohd. Muji, Siti Zarina; Abdul Rahim, Ruzairi; Rahiman, Mohd Hafiz Fazalul; Zakaria, Zulkarnay; Mohamad, Elmy Johana; Karis, Mohd Safirin (IFSA, 2011)
The aim of this paper is to show the linearization of optical sensor. Linearity of the sensor response is a must in optical tomography application, which affects the tomogram result. Two types of testing are used namely, testing using voltage parameter and testing with time unit parameter. For the former, the testing is by measuring the voltage when the obstacle is placed between transmitter and receiver. The obstacle diameters are between 0.5 until 3 mm. The latter is also the same testing but the obstacle is bigger than the former which is 59.24 mm and the testing purpose is to measure the time unit spend for the ball when it cut the area of sensing circuit. Both results show a linear relation that proves the optical sensors is suitable for process tomography application.